2019
DOI: 10.29354/diag/112397
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the energy effectiveness of multistage differential gears when the speed is changed by the carrier

Abstract: The energy effectiveness of the multistage gear differential in the device for speed change by carrier has been investigated with the determination of the efficiency. Considering complexity of the problem, the analytical methods of efficiency determining for two-and three-stage differential gears have been obtained and proposed using the potential power method, when the driving link is the first-stage sun gear, the driven link is the ring gear of the last stage or vice versa, and the links of the speed change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Despite the great interest of researchers in determining the relationship between inclusions and strength, in particular fatigue strength, it was not possible to clearly define this relationship. The presented knowledge is based on hypotheses [38][39][40][41][42][43][44][45]. It was confirmed that the fatigue strength of metal alloys depends not only on its microstructure, but also on the quantity and quality of non-metallic inclusions.…”
Section: Introductionmentioning
confidence: 80%
“…Despite the great interest of researchers in determining the relationship between inclusions and strength, in particular fatigue strength, it was not possible to clearly define this relationship. The presented knowledge is based on hypotheses [38][39][40][41][42][43][44][45]. It was confirmed that the fatigue strength of metal alloys depends not only on its microstructure, but also on the quantity and quality of non-metallic inclusions.…”
Section: Introductionmentioning
confidence: 80%
“…Modern machines operate at high speeds and workloads, frequent changes in operating modes and overloads [1][2][3]. In such conditions, the development of devices for changing the speed and protection against overloads, capable with high load capacity and stability of characteristics to provide effective protection against overload is an important problem for mechanical engineering science.…”
Section: Actuality and Statement Of The Problemmentioning
confidence: 99%
“…A generatrix of the single or double helix type is proposed for describing the side surface of a wheel tooth to increase the contact length. Another constructive option for increasing energy efficiency by the example of differential mechanisms was proposed in [13].…”
Section: Literature Reviewmentioning
confidence: 99%